"Non-invasive" portable laser ablation sampling for lead isotope analysis of archaeological silver: a comparison with bulk and in situ laser ablation techniques. Issue 1 (1st December 2021) - Merkel, S. W.; D'Imporzano, P.; van Zuilen, K.; Kershaw, J.; Davies, G. R.
Abstract : Portable laser ablation is tested for Pb isotope analysis of silver, yielding results comparable to bulk analyses. This low impact method removes the need for invasive sampling, opening the way for analysis of archaeological silver worldwide. Abstract : The main factor restricting lead isotope analysis of metals from museum collections is the requirement for physical material. Hence, there are major incentives for developing minimally invasive methods for lead isotope analysis that are accurate and precise enough to reveal historical information about artefacts and their origin. Portable laser ablation (pLA), collecting microscopic samples on Teflon filters, has four key benefits. It produces no visual impact to the artefacts, does not require transport of artefacts to laboratory facilities, there are no artefact size restrictions, and samples are processed under clean laboratory conditions allowing Pb purification prior to measurement by solution MC-ICPMS. To validate the efficacy of the pLA technique on silver, nine matrixed-matched commercial, in-house and archaeological reference materials were sampled and analysed multiple times (9–10). The pLA mean analyses (±2SD) were all consistent with inter-laboratory bulk analyses. The digestion of sample filters produces precisions that are consistently more than five-times better than in situ nsLA-MC-ICPMS and are the same order of magnitude expected for bulk samples processed in different laboratories.